COMPARISON OF OPERATING COST PERFORMANCE BEFORE AND AFTER THE IMPLEMENTATION OF THE FUEL COST EFFICIENCY STRATEGY - Aryawan, Nyoman Sukma; Sedana, I. B. Pandji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.12.TAHUN.2022, 2022)
In this study, a comparison of operating cost performance before and after the implementation of the fuel cost efficiency program at PT Indonesia Power Grati POMU was conducted. In this study, the comparison of operating cost performance before and after the implementation of the fuel cost efficiency program for the variable costs of gas compression service PLTGU Grati, BPP component C and BOPO PLTG Block 2 dominantly uses CNG gas (reaching 55% of total CNG usage) will be tested. tested using the t-paired test and the Wilcoxon test. The data used is secondary data obtained from PLTGU Grati. From the test results, there are differences between the cost of compressing gas services for PLTGU Grati before and after the efficiency program as well as before and after renegotiation of tariffs. In addition, there are also differences in BPP and BOPO with gas fuel at PLTG Block 2 Grati between before and after the fuel cost efficiency program. Fuel cost efficiency program carried out at the PLTGU. . Grati has been able to reduce the use of compressed gas CNG energy by up to 78.49% or USD 3,707,713 within six months, equivalent to Rp. 51,907,976,400,00, as well as reducing the Cost of Generating to 14% and lowering the BOPO ratio by 7.1% so as to reduce the difference in the cost of the C gas component by Rp. 2,186,963,429.00 per month in the period from July to December 2019